Preparation method and application of CeO2-loaded Pd-based alloy heterogeneous nanowire
By preparing CeO2-loaded heterogeneous nanowires with CeO2-loaded Pd-based alloys under low temperature and normal pressure, the metal/metal oxide interface was constructed, and the problems of high cost and low utilization in the oxidation of glycol in the prior art were solved, and efficient glycolic acid yield and excellent catalytic performance were achieved.
Patent Information
- Application Number
- CN202411948500.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, precious metal Pd-based nanomaterials have high cost and low utilization in promoting oxidation of glycol, and it is difficult to effectively regulate the reaction path to improve glycolic acid yield.
Using a simple and easy-to-use water system synthesis method, Pd-based alloy heterogeneous nanowires supported by CeO2 were prepared under low temperature and normal pressure, and the metal/metal oxide interface was constructed to optimize the catalytic reaction path.
The oxidation activity of palladium-based catalysts and the selectivity of glycolic acid under alkaline conditions were improved, and the activity and superior selectivity were significantly improved, and the stability was also significantly improved.
Smart Images

Figure CN119710817A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials and their preparation and application, and in particular to a method for preparing CeO2-loaded Pd-based alloy heterogeneous nanowires and their application as electrocatalysts in ethylene glycol oxidation reaction (EGOR). Background Art
[0002] Glycolic acid is an α-hydroxy acid and an important chemical substance with the smallest molecular weight among α-hydroxy acids. As a high value-added substance, glycolic acid has a wide range of applications in agriculture, biology, chemistry and other fields. Glycolic acid has a wide range of sources, one of which is the intermediate product produced in the oxidation process of ethylene glycol. Ethylene glycol is a low-toxic, low-cost, high-boiling-point, high-energy-density liquid fuel, which is particularly attractive in the contemporary era of promoting green and efficient development. If ethylene glycol is to be oxidized in the direction of generating glycolic acid, it is essential to be able to regulate the selectivity of electrocatalysts. As the mainstay of recognized electrocatalysts, precious metal Pd-based nanomaterials play a great role in promoting the oxidation of ethylene glycol. Reducing its cost and improving its utilization rate have become urgent problems to be solved. Commonly used effective strategies include introducing multi-component systems and constructing special structures. As a typical multi-component substance, alloys can reduce the activation energy of catalytic reactions and change the internal electronic properties of atoms to produce synergistic effects. In addition, metal oxides usually have high chemical and thermal stability and have unique advantages in regulating electrochemical reaction pathways.
[0003] The electrocatalytic performance of nanomaterials can be further optimized by increasing the number of active sites on one-dimensional nanowires, where the active sites are fully exposed and new active sites can be formed through the presence of interfaces. When metals and metal oxides form an interface, the metal can provide higher conductivity, while the metal oxide provides a unique electronic structure to compensate for the lack of conductivity. In addition, metal oxides are relatively stable and can extend the service life of nanocatalysts. The combination of the two can also optimize the reaction path and improve the selectivity of the target product. Therefore, it is crucial to prepare an alloy nanowire containing a metal / metal oxide interface to regulate the ethylene glycol oxidation path and increase the yield of glycolic acid. Summary of the invention
[0004] To solve the problems raised in the above background technology. The purpose of the present invention is to provide a method for preparing CeO2-loaded Pd-based alloy heterogeneous nanowires; the preparation method adopts a simple and easy water system synthesis method, and obtains a one-dimensional heterogeneous nanomaterial by a simple hydrothermal synthesis method at low temperature and normal pressure. The method is simple to operate and has strong repeatability.
[0005] Another object of the present invention is to provide a Pd-based alloy heterogeneous nanowire loaded with CeO2 prepared by the above method.
[0006] Another object of the present invention is to provide the use of the above-mentioned Pd-based alloy heterogeneous nanowires loaded with CeO2 as an electrocatalyst in regulating the EGOR reaction pathway.
[0007] To achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing CeO2-loaded Pd-based alloy heterogeneous nanowires, comprising the following steps: Preparation of PdAgPb nanowires After the surfactant is heated and dissolved, a palladium source, a silver salt, and a lead salt are added and mixed evenly, and the mixture is allowed to stand at a constant temperature. After cooling, thin and uniform PdAgPb nanowires are obtained.
[0008] (2) Preparation of Pd-based alloy heterogeneous nanowires loaded with CeO2 A cerium source and L-arginine were added to the prepared PdAgPb nanowires, and the mixture was kept warm for reaction and then cooled to room temperature. The mixture was washed, centrifuged several times, and freeze-dried to obtain the product PdAgPb / CeO2 NWs heterostructure.
[0009] The preparation method of the CeO2-loaded Pd-based alloy heterogeneous nanowires of the present invention is carried out in a water system by a simple and easy synthesis method. The preparation method has simple conditions, strong repeatability, simple operation and high feasibility.
[0010] Furthermore, in step (1), the molar ratio of the palladium source, the silver salt and the lead salt is 9:1:1; and the molar ratio of the surfactant to the palladium source is 1:175-176.
[0011] Furthermore, in step (1), the palladium source is prepared by PdCl2 and HCl, and deionized water is added to prepare 0.01 mol L -1 The chloropalladic acid H2PdCl4; the silver salt is AgNO3; the lead salt is Pb(NO3)2.
[0012] Furthermore, in step (1), the surfactant is dioctadecyl dimethyl ammonium chloride.
[0013] Furthermore, in step (1), the temperature of the constant temperature standing is 80-95° C., and the time of the constant temperature standing is 1-3.5 hours.
[0014] Furthermore, in step (2), the molar ratio of the cerium source to the palladium source in step (1) is 1:1.6-1.8; and the molar ratio of the palladium source in step (1) to L-arginine is 1:1.6.
[0015] Furthermore, in step (2), the cerium source is Ce(NO3)3·6H2O.
[0016] Furthermore, in step (2), the temperature of the heat preservation and standing is 80-95° C., and the time of the constant temperature standing is 1-3.5 hours.
[0017] Furthermore, in step (2), the washing solution is a mixed solution of ethanol and water.
[0018] The present invention also provides a CeO2-loaded Pd-based alloy heterogeneous nanowire prepared by the above preparation method. The CeO2-loaded Pd-based alloy heterogeneous nanowire PdAgPb nanowire has a width of 3.0 nm, a CeO2 nanoparticle size of about 2.5 nm, and an alloy nanolattice of about 0.231 nm to 0.233 nm.
[0019] The present invention also provides a use of the CeO2-loaded Pd-based alloy heterogeneous nanowire as described above as an electrocatalyst in alkaline ethylene glycol oxidation.
[0020] The regulation performance of the nanocatalyst obtained by the present invention was investigated by using glycolic acid, one of the products of the ethylene glycol oxidation reaction, as a probe reaction. The target product is obtained simply and quickly by using the preparation method of the present invention, and the deficiency of a single component is compensated by constructing a heterogeneous interface, introducing metal oxides and non-metallic elements, and forming alloys. In the present invention, the nanowires are synthesized by three metal elements, Pd, Ag, and Pb, and cerium oxide particles grow on the surface of the nanowires. Metal alloying can adjust the atomic arrangement and electronic structure of the Pd-based catalyst, and the structure has a synergistic effect and an electronic effect. In the catalytic ethylene glycol oxidation reaction, Ag and Pb both transfer electrons to Pd. At the same time, after the metal oxide cerium oxide is added to the solution and acts, the electrons are captured by cerium oxide. This multi-level electron transfer creates a more complex charge distribution on the interface, which helps to improve the conductivity of the material, adjust the adsorption energy of the reactant and the stability of the intermediate, and then change the reaction path and selectivity. Therefore, by introducing metal oxides to form a multiphase interface, the electron transfer process of the material can be optimized, thereby improving the performance and selectivity of the catalyst.
[0021] The oxidation peak and glycolic acid selectivity of PdAgPb / CeO2 NWs in the present invention are the highest in the corresponding system, and have the best mass activity. The measured data are normalized and are about 4.81 times that of commercial Pd / C. The stability is also the best. After 5000s of it test, the final residual mass activity of the sample of the invention is the highest. Compared with the prior art, the present invention has the following beneficial effects: The preparation method of the present invention is a simple method for preparing CeO2-loaded Pd-based alloy heterogeneous nanowires at a relatively low temperature and normal pressure by a soft template method, and the advantages of the synergistic effect, clear interface structure, ultrafine nanowires and ultra-small nanoparticles on improving the electrocatalytic activity are discussed. The results show that the addition of the formed alloy nanowires and metal oxide CeO2 enhances the ethylene glycol oxidation activity and the selectivity of glycolic acid of the palladium-based catalyst under alkaline conditions.
[0022] The present invention proposes a simple hydrothermal synthesis method of PdAgPb / CeO2 NWs, which introduces metal oxide cerium oxide rich in oxygen vacancies. Based on the many advantages of traditional one-dimensional noble metal nanowires, the PdAgPb alloy is combined with the noble metal Pd to construct a unique nanostructure interface. As an enhanced electrocatalyst, PdAgPb / CeO2 NWs has good catalytic activity and selectivity in an alkaline environment, and can oxidize cheap ethylene glycol to glycolic acid, which has great practical value. When conducting EGOR electrocatalysis, the catalyst with the best elemental composition and interface distribution showed significantly improved activity (7.6 Amg Pd -1 ) and superior glycolic acid selectivity (Faraday efficiency 89%), which are exceptional compared with many reported catalysts. The excellent performance of this catalyst depends on the complex and rich electron transfer, interatomic synergy and necessary interface effects, which together contribute to the high performance and precise oxidation path regulation of PdAgPb / CeO2 NWs in the field of alcohol oxidation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The structure diagram of the surfactant required for Example 1 of the present invention; Figure 2 TEM image of PdAgPb / CeO2 nanowires prepared in Example 2 of the present invention; Figure 3 HRTEM image of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention; Figure 4 This is the XRD pattern of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention; Figure 5 This is a selected area diffraction pattern of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention; Figure 6 This is an element mapping diagram of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention; Figure 7Cyclic voltammetry curves of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3 and 20% Pd / C catalyst in KOH solution; Figure 8 Impedance diagrams of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3 and a 20% Pd / C catalyst; Fig. 9 EGOR cyclic voltammetry curves of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3 and 20% Pd / C catalyst; Fig.10 EGOR variation diagram of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3 and 20% Pd / C catalyst at different scan rates; Fig.11 EGOR activation energy diagram of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3 and 20% Pd / C catalyst; Fig.12 The constant potential stability diagram of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3 and 20% Pd / C catalyst at a voltage of -0.2 V; Fig.13 The hydrogen spectra of the products of ethylene glycol oxidation catalyzed by the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3 and 20% Pd / C catalyst; Fig.14 Graph showing the selectivity of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2 of the present invention, Comparative Example 1, Comparative Example 2, Comparative Example 3 and 20% Pd / C catalyst to glycolic acid. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0025] Preparation of one-dimensional PdAgPb nanowires In a 40 mL empty glass bottle, weigh 0.015 g of dioctadecyl dimethyl ammonium chloride and dissolve it in 10 mL of deionized water. Then add 0.45 mL of 0.01 mol L -1 0.05 mL of chloropalladic acid aqueous solution with a concentration of 0.01 mol L -1 0.05 mL of silver nitrate aqueous solution with a concentration of 0.01 mol L -1 The lead nitrate aqueous solution was mixed evenly and placed in a 95°C oven at a constant temperature for 1 hour. After the reaction was completed, the temperature was naturally lowered.
[0026] The structure of surfactant is shown in Figure 1 shown. Example 2
[0027] Preparation of CeO2-loaded Pd-based alloy heterogeneous nanowires 0.005 g of cerium nitrate particles were added to the nanowires in Example 1 above, and an alcohol-water mixture (5 mL + 5 mL) was added to dissolve the nanowires. Then, 1.4 mg of L-arginine was added dropwise under stirring, and the nanowires were placed in an oven at 80°C and kept warm for 3.5 h. After the reaction, the nanowires were washed with a mixed solution of ethanol and water, and centrifuged and dried to obtain the product, Pd-based alloy heterogeneous nanowires loaded with CeO2 (PdAgPb / CeO2 nanowires).
[0028] The volume ratio of alcohol to water in the alcohol-water mixture is 1:1.
[0029] The TEM image of the prepared PdAgPb / CeO2 nanowires is shown in Figure 2 As shown, low-power electron microscopy shows that the product has high purity, the nanowires are evenly dispersed, and the thickness is about 3nm, maintaining the ultra-thin characteristics of PdAgPb NWs; the grown cerium oxide nanoparticles are also clearly and evenly dispersed on the surface of the nanowires, with an average particle size of about 2.5nm.
[0030] Attached Figure 3 This is the HRTEM image of the product. The lattice spacing of the nanowires was measured by software, which confirmed that the metal formed an alloy during the reaction and that the cerium oxide nanoparticles and the nanowires formed a clear heterogeneous interface.
[0031] Attached Figure 4The XRD diagram of the product. According to the XRD standard card analysis, PdAgPb NWs has four obvious characteristic peaks, representing the (111), (200), (220) and (311) crystal planes of the precious metals in the material. When cerium oxide is added, its XRD characteristic peaks appear. By comparison, the (111) and (222) crystal planes of cerium oxide can be seen respectively. Compared with pure alloy nanowires, the characteristic peak position of the alloy has also shifted, which fully proves the successful synthesis of the PdAgPb / CeO2 NWs heterostructure and the electron transfer during the product formation process.
[0032] Attached Figure 5 This is a selected area electron diffraction pattern, which clearly shows different crystal planes.
[0033] Attached Figure 6 This is the element mapping diagram, from which it can be seen that the four elements are evenly distributed in the heterostructure nanowires. Example 3
[0034] Application of CeO2-loaded Pd-based alloy heterojunction nanowires as electrocatalysts in EGOR.
[0035] The testing method of CeO2-loaded Pd-based alloy heterogeneous nanowires as electrocatalysts for EGOR is as follows: The test method of the CeO2-loaded Pd-based alloy heterogeneous nanowires prepared in Example 2 as electrocatalysts for catalyzing EGOR is as follows: Preparation of test electrodes Weigh 2.0 mg of the PdAgPb / CeO2 nanoheterostructure prepared in Example 2, add 8.0 mg of XC-72R carbon (Cabot), prepare an ink solution with a metal mass fraction of 20%, mix thoroughly, centrifuge and dry. Dissolve the above catalyst in a mixed solution of ethanol and water (1:3), add 0.005 mL of naphthol, mix thoroughly, and finally obtain a metal concentration of 1.0 mg mL -1 Take 0.003mL of the prepared catalyst and drop it on a clean glassy carbon electrode. After natural drying, it can be used for electrochemical EGOR testing.
[0036] For this EGOR test, a cyclic voltammetry test was first performed in a 1.0 M KOH solution saturated with N2, with a scan voltage range of 0.2 to 0.9 V (vs. SCE). After the scan curve stabilized, a cyclic voltammetry test was performed in a 1 M KOH and 1 M EG mixed solution saturated with N2. The scan rate was always set to 5 mV s -1 .
[0037] The electrocatalytic EGOR performance test results of the CeO2-loaded Pd-based alloy heterogeneous nanowires of the present invention are as follows: Figure 7 , 8 , as shown in Figure 9. The electrochemically active surface area can preliminarily reflect the catalytic performance of the catalyst material. It is obvious from the figure that Example 2 has the highest electrochemical activity. Therefore, it has the most active sites and the highest material utilization rate, and theoretically can catalyze the reaction more effectively. The electrochemical impedance test shows that the h-PdAgPb / CeO2NWs of Example 2 has a relatively low electrochemical impedance, indicating that the surface is active and has high electrical conductivity, and the electrocatalytic reaction is more likely to occur on its surface, which also shows that the presence of the interface accelerates the reaction kinetics. Combined with the study of electrochemically active surface area and impedance, its electrocatalytic alcohol oxidation activity should also be the highest, as shown by the CV curve of the ethylene glycol oxidation peak and the intermediate product removal peak of the mixed solution of 1M potassium hydroxide and 1MEG. The catalytic ethylene glycol oxidation activity of h-PdAgPb / CeO2NWs can reach 7.6A mg Pd -1 Compared with comparative example 1, comparative example 2, comparative example 3 and commercial palladium carbon, the values are 2.42, 2.76, 2.22 and 4.81 times higher respectively, as shown in Table 1 for details.
[0038] The test results of the activation energy and diffusion kinetics performance of the CeO2-loaded Pd-based alloy heterogeneous nanowire electrocatalytic EGOR are as follows: Fig.10 , 11 As shown. The electrochemical kinetic state was measured by adjusting the scan rate at room temperature. In a mixed solution of 1M potassium hydroxide and 1M EG, CV curves at different scan rates were obtained. The activity of electrocatalytic ethylene glycol increases with the increase of the scan rate. The slope of h-PdAgPb / CeO2 NWs has a controlling effect on the catalyst kinetics, among which the slope of Example 2 is the largest, indicating that they can significantly accelerate the diffusion of various substances (including intermediates) during the reaction. By maintaining 50mV / s and adjusting the catalytic environment temperature, the CV curve in a mixed solution of 1M potassium hydroxide and 1M EG was obtained. The mass activity of each catalyst varies with the change of temperature. Among them, the Ea value of Example 2 is the smallest, only 19.15 KJmol -1 This indicates that h-PdAgPb / CeO2 NWs has the lowest energy barrier for the catalytic oxidation of ethylene glycol.
[0039] The stability test results of the electrocatalytic EGOR performance of the CeO2-loaded Pd-based alloy heterogeneous nanowires of the present invention are as follows: Fig.12 As shown in the figure, the activities of several catalysts decreased to varying degrees after 5000s scanning, and then tended to be stable. The decrease in Example 2 was the smallest. The final remaining mass activity and the long plateau period showed that the catalyst had good stability.
[0040] The selectivity test results of the electrocatalytic EGOR performance of the CeO2-loaded Pd-based alloy heterogeneous nanowires of the present invention are as follows: Fig.13 , 14 The ethylene glycol products catalyzed by the catalysts of Example 2 and the comparative examples were subjected to nuclear magnetic resonance testing, and the 1H NMR spectra obtained were as follows: Fig.13 As shown. Among the products, glycolic acid peak is the most significant. The calculated glycolic acid selectivities of h-PdAgPb / CeO2NWs, m-PdAgPb / CeO2 NWs, h-Pd / CeO2NWs and PdAgPb NWs are 15%, 42%, 79.8% and 89%, respectively. Compared with h-Pd / CeO2 NWs and PdAgPb NWs, h-PdAgPb / CeO2 NWs and m-PdAgPb / CeO2 NWs with the introduction of cerium oxide show significantly improved selectivity.
[0041] Table 1 Comparison of catalytic performance of palladium-based ethylene glycol electrocatalysts
[0042] In summary, PdAgPb / CeO2NWs heterostructures have considerable advantages in improving the selectivity of ethylene glycol oxidation to glycolic acid. This strategy highlights the ease of synthesizing low-dimensional nanostructures and the advantages of metal / metal oxide heterogeneous interfaces, and promotes the development of metal alloy-based heterogeneous nanowires based on PdAgPb / CeO2NWs. The results show that PdAgPb / CeO2 NWs not only have good versatility in the oxidation of alcohols, but also reduce the catalytic activation energy and accelerate the electrochemical diffusion rate. At the same time, they show good stability due to the synergistic and electronic effects of metal alloys and the extremely abundant oxygen vacancies in metal oxides. The activity decays slowly during long-term use, providing a certain basis for designing more efficient fuel cells. These catalysts have high selectivity for directing the oxidation of ethylene glycol to value-added glycolic acid, and can produce high-value, versatile glycolic acid and related chemicals at low cost and with minimal losses. Comparative Example 1
[0043] In a 40 mL empty glass bottle, weigh 0.015 g of dioctadecyl dimethyl ammonium chloride and dissolve it in 10 mL of deionized water. Then add 0.45 mL of 0.01 mol L -1 0.05 mL of chloropalladic acid aqueous solution with a concentration of 0.01 mol L -1 0.05 mL of silver nitrate aqueous solution with a concentration of 0.01 mol L -1The lead nitrate aqueous solution was mixed evenly and placed in a 95℃ oven for 1 hour. After the reaction was completed, the temperature was lowered. Then, the cerium nitrate nanoparticle solution was added and physically stirred and mixed evenly. Then, it was washed with a mixed solution of ethanol and water, and the product m-PdAgPb / CeO2 NWs nanoheterostructure was obtained after centrifugal drying. Comparative Example 2
[0044] In a 40 mL empty glass bottle, weigh 0.015 g of dioctadecyl dimethyl ammonium chloride and dissolve it in 10 mL of deionized water. Add 0.45 mL of 0.01 mol L -1 chloropalladic acid aqueous solution, mix well and put into 95℃ oven for 1h, and cool down after the reaction. 0.005g cerium nitrate particles were added to the nanowires, and 1:1 alcohol-water mixture was added to dissolve, and L-arginine was added dropwise under stirring, and the nanowires were placed in an 80℃ oven for 3.5h; after the reaction, they were washed with a mixed solution of ethanol and water, and the product h-Pd / CeO2NWs was obtained after centrifugal drying. Comparative Example 3
[0045] In a 40 mL empty glass bottle, weigh 0.015 g of dioctadecyl dimethyl ammonium chloride and dissolve it in 10 mL of deionized water. Then add 0.45 mL of 0.01 mol L -1 0.05 mL of chloropalladic acid aqueous solution with a concentration of 0.01 mol L -1 0.05 mL of silver nitrate aqueous solution with a concentration of 0.01 mol L -1 The lead nitrate aqueous solution was mixed evenly and placed in a 95°C oven at a constant temperature for 1 hour. After the reaction was completed, the temperature was programmed to cool down to obtain PdAgPb NW nanowires.
[0046] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0047] It should be noted that the above content only illustrates the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing CeO2-loaded Pd-based alloy heterogeneous nanowires, characterized in that: The following steps are involved: (1) Preparation of PdAgPb nanowires After the surfactant is heated and dissolved, a palladium source, a silver salt, and a lead salt are added and mixed evenly, and then allowed to stand at a constant temperature and then cooled to obtain thin and uniform PdAgPb nanowires; (2) Preparation of Pd-based alloy heterogeneous nanowires loaded with CeO2 A cerium source and L-arginine were added to the prepared PdAgPb nanowires, and the mixture was kept warm for reaction and then cooled to room temperature. The mixture was washed, centrifuged several times, and freeze-dried to obtain a PdAgPb / CeO2 NWs heterostructure.
2. The method for preparing a CeO2-loaded Pd-based alloy heterogeneous nanowire according to claim 1, characterized in that: In step (1), the molar ratio of the palladium source, the silver salt and the lead salt is 9:1:1; and the molar ratio of the surfactant to the palladium source is 1:175-176.
3. The method for preparing a CeO2-loaded Pd-based alloy heterogeneous nanowire according to claim 1, characterized in that: In step (1), the palladium source is prepared from PdCl2 and HCl, and deionized water is added to make it 0.01 mol L -1 The silver salt is AgNO3; the lead salt is Pb(NO3)2.
4. The method for preparing a CeO2-loaded Pd-based alloy heterogeneous nanowire according to claim 1, characterized in that: In step (1), the surfactant is dioctadecyl dimethyl ammonium chloride.
5. The method for preparing a CeO2-loaded Pd-based alloy heterogeneous nanowire according to claim 1, characterized in that: In step (1), the temperature of the constant temperature static state is 80-95° C., and the time of the constant temperature static state is 1-3.5 h.
6. The method for preparing a CeO2-loaded Pd-based alloy heterogeneous nanowire according to claim 1, characterized in that: In step (2), the molar ratio of the cerium source to the palladium source in step (1) is 1:1.6-1.8; the molar ratio of the palladium source in step (1) to L-arginine is 1:1.
6.
7. The method for preparing a CeO2-loaded Pd-based alloy heterogeneous nanowire according to claim 1, characterized in that: In step (2), the cerium source is Ce(NO3)3·6H2O.
8. The method for preparing a CeO2-loaded Pd-based alloy heterogeneous nanowire according to claim 1, characterized in that: In step (2), the temperature of the heat preservation and standing is 80-95° C., and the time of the constant temperature standing is 1-3.5 hours; and the washing solution is a mixed solution of ethanol and water.
9. A CeO2-loaded Pd-based alloy heterogeneous nanowire prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the CeO2-loaded Pd-based alloy heterogeneous nanowires as claimed in claim 9 as an electrocatalyst in alkaline ethylene glycol oxidation.
Citation Information
Patent Citations
Palladium-lead alloy nanowire, palladium-lead alloy nanowire catalyst and preparation method of palladium-lead alloy nanowire catalyst
CN115608979A
Preparation method and application of low-dimensional CeO2-based Pd alloy heterogeneous nanostructure
CN117512680A